The language learning style preferences of selected Chiang Kai Shek college students: A comparative study across culture and gender - Calamaza, Nolita R. (Animo Repository, 2002)
This research investigates the language learning style preferences of a selected group of students from different cultures (Chinese, Chinoys, Pinoys, and Taiwanese) studying at Chiang Kai Shek College. It also aims to find out if the language learning style preferences of the students differ according to culture and gender. Beatrice's Learning Style Inventory is modified to suit the objectives of the study. Purposive sampling is used in the selection of the student-respondents. Ninety-eight (98) students from different cultural backgrounds have taken the modified English Language Learning Style Inventory (ELLSI) to identify their language learning style preferences. The ELLSI is composed of 15 items and each item has three categories: visual language learning style, auditory language learning style, and kinesthetic or tactile language learning style. The study employs a descriptive-comparative design. The students' English language learning style preferences are determined using frequencies and percentages. Repeated measures design of the ANOVA family is used to ascertain if there is a difference in the English language learning style preferences across culture groups and gender. The hypothesis is tested at .05 level. It has been found that most of the subjects prefer the visual modality - they perceive and process information through listening.